A novel Voice Priority Queue (VPQ) scheduler and algorithm for VOIP over WLAN network - Nizar, Kashif; Hassan, Suhaidi; M. Kadhum, Mohammed (Universiti Teknikal Malaysia Melaka, 2011)
The VoIP deployment on Wireless Local Area Networks (WLANs), which is based on IEEE 802.11 standards, is increasing.Currently, many schedulers have been introduced such as Weighted Fair Queueing (WFQ), Strict Priority (SP) General processor sharing (GPS), Deficit Round Robin (DRR), and Contention-Aware Temporally fair Scheduling(CATS).Unfortunately, the current scheduling techniques have some drawbacks on real-time applications and therefore will not be able to handle the VoIP packets in a proper way.The objective of this research is to propose a new scheduler system model for the VoIP application named final stage of Voice Priority Queue (VPQ) scheduler.The scheduler system model is to ensure efficiency by producing a higher throughput and fairness for VoIP packets.In this paper, only the final Stage of the VPQ packet scheduler and its algorithm are presented.Simulation topologies for VoIP traffic were implemented and analyzed using the Network Simulator (NS-2).The results show that this method can achieve a better and more accurate VoIP quality throughput and fairness index over WLANs.